Trade integration amongst APEC : realism in near future? - Chua, Hui Ling. (2009)
The paper seeks to analyse the possibility of trade integration amongst member countries in the Asia-Pacific Economic Cooperation [APEC] over 3 periods from 1981 to 2007. By graphing the openness of these countries, we observe rising potential of trade integration. From our calculations of Readiness Indicators and the Krugman Index, we observe that APEC countries are ready in economic structure for trade integration. Our estimates for the labour adjustment duration also justify the high possibility of trade integration for APEC members. Prior to our regression, we conducted a Bartlett Kernel test and found that our model is stationary. Theoretically, business cycle of countries converges with facilitation of trade. Through the attempt to establish fixed effect models of APEC countries with United States, Japan and China as anchor countries, we determine that business cycles synchronisation to bring about trade integration can be facilitated with intra-industry trade but the relationship with trade intensity, fiscal and monetary coordination are deemed uncertain.